Employment sector and pay gaps: genetic and environmental influences - Terhi Maczulskij (European Regional Science Association (ERSA), 2012)
This paper examines the role of genetic factors and shared environment in explaining the choice of working in the public sector and public-private sector pay gaps. The analyses are done using data for Finnish twins that span the period from 1990 to 2004. The data are based on two sources. The first data are Finnish Twin Cohort conducted by Department of Public Health in University of Helsinki. These data have been matched with the Finnish Longitudinal Employer-Employee Data (FLEED) kept by Statistics Finland. The standard behavioural genetics decomposition and DF (DeFries and Fulker 1985) analyses indicate that public sector employment is broadly influenced by the genetic factors by around 40 per cent, while the role of shared environment remains statistically zero. The results are robust across gender and different specifications. In the extended DF-analysis, the inclusion of potential confounders drops the point estimate of heritability to some 30 per cent for both sexes, and the education years and education field play a notable part of this respect. In other words, genetic factors might affect individuals to engage public sector employment through at least one obvious mechanism – educational outcomes. The model that treats all twins as individuals suggests that females receive a pay disadvantage of 4 per cent in the public sector, while the pay gap is somewhat higher for males being 7 per cent. The within-twin pair model for males yields a pay gap of zero – both in statistical and economical sense – and the difference in estimated pay gaps is mainly caused by the genetic factors, such as ability. This result indicates that private sector attracts relatively more able male workers that do the public sector. The results for females indicate that the pay gap is also zero, when all the family-specific effects are held constant in the analysis. However, the point estimate is -0.048, which give some evidence that there is an economical significance in the pay gap of approximately 5 per cent, and that neither the role of genetics nor shared environment plays a significant role in understanding the pay gap between the public and private sectors for females.
Keywords: J45; J13; J24; 330; public sector employment; behavioural genetics; twin studies